Obligation to Keep Confidential Notary Position in Criminal Jurisdiction Process Forgiven Rights & Refuse Obligations - Suhendri Suhendri; Arpangi Arpangi (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
A notary occasionally receives false information from some parties, and then it becomes the basis of the making of authentic Notarial Deed. Notary criminal liability on the Notarial Deed based on false information should be analyzed and examined as well as its legal impacts. Based on the result of this research, it can be identified that a notary cannot be asked for his or her criminal liability related to the making of Notarial Deed based on false information from certain parties, and it cannot fulfill the formulation of counterfeiting criminal act in article 266 paragraph (1) jo. article 55 paragraph (1) of the Criminal Code. A notary can be asked for his or her criminal liability related to his or her Notarial Deed he or she made based on what he or she has seen, witnessed, or experienced in committing a criminal act on purpose, or Negligence; a notary makes a false Notarial Deed and he or she inflicts other parties. Referring to a criminal liability, a notary should fulfill the following elements; a criminal act, ability to be responsible for, committing an act on purpose or absence, and there is no reason for apology. A notary Notarial Deed based on false information does not automatically make the document itself invalid. The party who is inflicted by this document can propose a civil action to the Court of Justice in order to cancel the document. A notary criminal liability should be regulated in the next Notary Authority Act (UUJN).